Research progress on the effects of early anesthesia exposure on neurodevelopment in children - DAI Ziyi, MA Lulu, HUANG Yuguang (Jichu yixue yu linchuang, 2023)
General anesthetics can induce neuronal apoptosis, cause structural changes in the developing brain, and lead to long-term cognitive and behavioral changes. However, the effects of early anesthesia exposure on children's intelligence, behavior and neuroimaging outcomes are not consistent in clinical studies, which suggested the complex mechanism of nerve injury caused by early exposure of anesthesia in children. This review summarized the Results from animal studies and clinical evidence in recent years, discussed the potential mechanism of the effect of early anesthesia exposure on neurodevelopment in children, in order to guide the treatment of children and the choice of operation time.